Effect of Ramadan Fasting on Patients With Type Ii Diabetes Mellitus (A Literature Review) - Andriyani Asmuni; Masyitoh Masyitoh; Ahmad Khoirul Fajri; Muhammad Farid Hamzen; Rohimi Zamzam; Ernyasih Ernyasih; Abul A’la Al Maududi; Dihartawan Dihartawan (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Diabetes Mellitus (DM) or commonly known as diabetes is a disease caused by impaired carbohydrate metabolism due to the pancreas cannot produce insulin or can produce insulin but the body is not able to use insulin effectively and also produces less insulin, so the body is unable to metabolize carbohydrates, fats, and proteins due to insulin deficiency. Insulin is a hormone that regulates the balance of blood glucose in the body. The writing of this article uses a method of literature review or review literature by reviewing several journals and articles about the relationship between fasting and control of diabetes mellitus management. Journals are downloaded or obtained through the journal portal of universities in Indonesia. The process of writing this article is carried out for two weeks. The results showed that Ramadan fasting is related to DM control through DM management. The conclusion is that there is a significant relationship between several journals studied.